SHARIAH AND CORPORATE SOCIAL RESPONSIBILITY: A COMPARATIVE ANALYSIS OF SHARIAH-COMPLIANT BUSINESSES IN INDONESIA AND MALAYSIA - Haruni Ode; Imron Natsir; Eko Cahyo Mayndarto (Yayasan Adra Karima Hubbi, 2025)
The integration of Shariah principles with corporate social responsibility (CSR) has gained prominence as businesses strive to align ethical practices with Islamic values. Indonesia and Malaysia, as leading Muslim-majority economies with robust Islamic finance sectors, offer unique insights into how Shariah compliance influences CSR frameworks. However, comparative studies on CSR practices among Shariah-compliant businesses in these countries remain limited, particularly in addressing cultural, regulatory, and theological divergences. This study aims to analyze and compare CSR practices in Shariah-compliant businesses in Indonesia and Malaysia, focusing on their alignment with Islamic ethical principles, stakeholder engagement, and contributions to sustainable development. A mixed-methods approach is employed, combining quantitative analysis of CSR reports from 50 companies (25 per country) and qualitative interviews with 20 stakeholders (executives, Shariah scholars, and CSR experts). Data were analyzed using thematic analysis and comparative statistical tools. The findings reveal that Malaysian businesses exhibit more standardized CSR frameworks rooted in stringent Shariah governance, emphasizing environmental sustainability and ethical governance. Indonesian businesses prioritize community-driven initiatives, reflecting local socio-cultural contexts.